240 First year experience of hereditary testing in gynecological cancer patients in a clinical setting in the bahamas. (18th September 2019) - Bowe, S; Butler, R; Halliday, D; Geremias, R; Cerbon, D; Huang, M; Roberts, R; Schlumbrecht, M; Slomovitz, B; George, S
Abstract : Objectives: In a previous cohort of predominantly breast cancer patients, ∼25% of cases had 7 recurrent mutations in BRCA1 and BRCA2.The rate of hereditary ovarian cancer in the Bahamas was sought using an Oncology-led point of genetic testing at the Princes Margaret Hospital (PMH) in the Bahamas. Methods: Women were counseled and consented for genetic testing in the Gynecology Oncology clinic at our facility. Saliva samples underwent next generation sequencing (NGS) in a CLIA approved external laboratory. A 30 gene panel linked to breast, ovarian and/or uterine cancer risks was used to identify: BRCA1, BRCA2, Lynch genes, MLH1, MSH2, MSH6, PMS2, EPCAM, MUTYH, APC, STK11, PALB2, MITF, BAP1, CDKN2A, TP53, BMPR1A, SMAD4, POLD1, POLE1, CHEK2, PTEN, CDH1, BRIP1, CDK4, GREM1, RAD51C, RAD51D, PMS2, NBN and BARD1 . Reportsincluded presence or absence of deleterious mutations and variants of unknown significance (VUS). Results: Between 03/2018–03/2019, 28 women were tested, 17 women had ovarian cancer, 7 endometrial cancer, 2 breast cancer, and 2 women with a strong family history of ovarian cancer. The mean age at testing was 60 years. 21.4% had a deleterious mutation in BRCA: 5 in BRCA1 and 1 in BRCA2. Of the patients with BRCA mutation 5/6 women were diagnosed with ovarian cancer (29.5%) and 1/6 had ductal carcinoma of the breast. Conclusions: Genetic testing at point of care in the Bahamas is feasible and acceptable. Results highlight need for universal hereditary screening for women in the Bahamas with ovarian cancer as this can allow for better treatment options.